1988
DOI: 10.1164/ajrccm/137.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Association between Nonspecific Bronchial Hyperreactivity and Superoxide Anion Production by Polymorphonuclear Leukocytes in Chronic Air-Flow Obstruction

Abstract: Inflammatory reactions are believed to be important in nonspecific bronchial hyperreactivity (BHR). To investigate the potential role for oxidant-mediated modulation of BHR, we investigated oxidative metabolism of polymorphonuclear leukocytes (PMN) from the peripheral blood in 28 nonallergic patients with chronic air-flow obstruction (CAO). No difference in O2- was found between 14 smokers and 14 ex-smokers with CAO. A significant correlation was found between the degree of BHR and O2(-)-generation of PMN afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
2
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(70 citation statements)
references
References 6 publications
7
59
2
2
Order By: Relevance
“…Moreover, a similar relationship has also been shown between the change in peripheral blood neutrophil count and the change in airflow limitation over time [25]. Similarly, an association between O 2 N-release by peripheral blood neutrophils and bronchial hyperresponsiveness in patients with COPD has been shown, suggesting a role for systemic ROS in the pathogenesis of the airway abnormalities in COPD [26]. Another study has shown a negative relationship between peripheral blood neutrophil luminol-enhanced chemiluminescence, as a measure of the release of ROS and measurements of airflow limitation in young cigarette smokers [27].…”
Section: Oxidative Stress In Bloodsupporting
confidence: 57%
“…Moreover, a similar relationship has also been shown between the change in peripheral blood neutrophil count and the change in airflow limitation over time [25]. Similarly, an association between O 2 N-release by peripheral blood neutrophils and bronchial hyperresponsiveness in patients with COPD has been shown, suggesting a role for systemic ROS in the pathogenesis of the airway abnormalities in COPD [26]. Another study has shown a negative relationship between peripheral blood neutrophil luminol-enhanced chemiluminescence, as a measure of the release of ROS and measurements of airflow limitation in young cigarette smokers [27].…”
Section: Oxidative Stress In Bloodsupporting
confidence: 57%
“…Cross-sectional studies investigating AHR in smokers and exsmokers with chronic bronchitis or COPD are presented in [81,82]. This suggests that AHR to histamine and methacholine does not revert to normal levels after smoking cessation in COPD, which could be due to either ongoing inflammation or irreversible structural changes in the lung.…”
Section: Chronic Bronchitis and Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…Only a few studies have investigated the effect of smoking on AHR in COPD patients. Two cross-sectional studies showed no differences in AHR to histamine or methacholine between exsmokers and smokers with COPD [12,13]. In contrast, the Lung Health Study showed that AHR to methacholine deteriorated to a smaller extend in quitters than in persistent smokers [14].…”
mentioning
confidence: 98%